Effects of Explicit Instruction on Incidental Noticing of Metaphorical Word Sequences during a Subsequent Reading Task - Mark Mueller, Charles (International Journal of English Studies, 2010)
Two experiments were conducted to determine whether explicit instruction focusing on metaphorical collocations would promote the incidental noticing of similar phrases by English learners during a subsequent reading task. Noticing was operationalized using the remember-know protocol and learning was measured on a fill-in-the-blanks test. In Experiment 1 (N = 36), within-subjects comparisons showed that explicit instruction led to more incidents of noticing (p < .001). Experiment 2 (N = 24) sought to extend the findings by examining whether self-referential questions during instruction would lead to greater noticing compared to depersonalized questions. Experiment 2 confirmed the first experiment’s finding of effects of explicit instruction on noticing, but failed to show significant effects for self-referential prompts on subsequent noticing, although such prompts did lead learners to produce higher word counts during the writing task. The two experiments suggest that explicit instruction promotes incidental noticing of important semantic contrasts in subsequent input.